EDUCATION AND PARTICIPATION OF STUDENTS AND THE COMMUNITY IN THE PRESERVATION OF MANGROVE ECOSYSTEMS AND THE CONSERVATION OF MIGRANT BIRDS IN TANJUNG PIAI NATIONAL PARK MALAYSIA - Sri Langgeng Ratnasari; Ramon Zamora; Asmaul Husna; Abdul Manan Nasution; Mochamad Iwan Kusnandar; Abdi Suramana Harahap; Dewi Fatmawati; Rasyid Hidayat Sagala; Marta Lova Diana; Ahmad Yasin; Hera Elrya Nurmawanti; Zulfadli; Kurniawan; Rabul Yamin; Surya Kusumah (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2026)
This community service program was conducted at Tanjung Piai National Park, Johor, Malaysia, with the objective of enhancing environmental awareness and promoting community participation in mangrove ecosystem preservation and migratory bird conservation. The program involved students and local community members through educational and participatory approaches, including environmental education, biodiversity observation, mangrove ecosystem exploration, and discussions on the ecological importance of migratory birds along the East Asian–Australasian Flyway. The activities were implemented over three days, encompassing preparation, field implementation, and evaluation stages. The results demonstrated an increase in participants’ knowledge and awareness regarding the ecological functions of mangroves as coastal protectors, biodiversity habitats, and carbon sinks. Participants also gained a better understanding of the significance of Tanjung Piai National Park as a critical stopover habitat for migratory birds. Furthermore, the program encouraged active community involvement in conservation initiatives, including ecosystem monitoring and environmental stewardship. The educational and participatory methods proved effective in fostering positive attitudes and behavioral changes toward environmental conservation. The program also strengthened collaboration among students, local communities, and park management authorities. Continuous support and multi-stakeholder cooperation are recommended to ensure the long-term sustainability of conservation efforts and environmental education initiatives in coastal ecosystems.